The relationship between the organizational culture and the individual attitude, particulary the question of individualism and collectivism - Szilágyi, Barabás (Acta Agraria Debreceniensis, 2008)
There is considerable consensus regarding the development of organizational culture; namely, that culture is the result of socialization, evolving through a social learning process. However, the mechanism of the process itself, along with the factors influencing it, raises a number of questions that are researched by different schools of thought. Some of the contextual factors that affect the development of culture, such as the characteristics of national culture or charismatic and other dominant people as role models, seem to be quite influential, especially when other influential factors affect these as well. Value analysis can be helpful for understanding the essence of organizational culture, and it can reveal underlying, hidden phenomena. The results of these studies depict organizational culture as a list of values or as a hierarchy. Values carry emotions as well, that may refer to their link with attitudes and to the fact that the two can be mixed up. The latest innovations in action and thought were the results of the political changes of the 1990s whose implications can be identified in both individual and national values. Changes of views and attitudes also emerge in the changes of collectivist-individualistic thinking and values which become part of the organizational culture and value structure according to value-centered analyses. The changing values define and influence our own opinions, identity, and, in turn, our behavior. Values reflected by our behavior and actions are to be guided by the harmony of individual, organizational, and national value systems. The lack of this synergy results in the dissonance of contrastive values and blocks actions. This, in turn, interferes with individual productivity and thus slows down organizational productivity as well. Our goal should be the synergy of values which creates the harmony of individual thinking and behavior since this harmony is the basis of success and productivity.